Underage Marriage Society 5.0 Perspective of Madzhab Syafi'i Fiqh and Marriage Law in Indonesia - Anwar Harianto; Moh. Muhibbin; Budi Parmono (Riviera Publishing, 2026)
Legal marriage is an absolute obligation according to Islamic teaching. However, these noble intentions often do not meet expectations if the husband and wife, or one of the partners, does not yet possess both physical and mental maturity. This unpreparedness can occur when someone marries while underage a phenomenon increasingly linked to the intensive use of gadgets by children in the Society 5.0 era. This research aims to determine the ruling on underage marriage in Society 5.0 according to the Shafi'i madhhab, as well as its relevance to Indonesian Marriage Law. The method used was normative legal research (library research), with primary materials drawn from the fiqh books of the Shafi'i school and Law No. 16 of 2019. The results show that underage marriage in Society 5.0 is considered valid (permissible) by the Shafi'i school, provided that a girl has reached the age of 15 or shows signs of puberty (menstruation or armpit hair growth), and for boys, the onset of wet dreams. The connection between the Shafi'i school and the Marriage Law lies in the age limit: the Shafi'i school sets the minimum age at 15 years, while the Marriage Law sets it at 19 years. Both regulations serve as legal justification for marriage dispensation. The conclusion is that underage marriage according to the Shafi'i school is valid by prioritizing maslahah, and the correlation between the two legal systems can be used to address cases of underage marriage in Society 5.0.